THE USE OF INNOVATIVE TECHNOLOGIES IN THE WORK OF THE CONCERT MASTER IN PRACTICAL CLASSES ON CHORAL CONDUCTING AND CHORAL CLASS IN CONDITIONS OF CONDITION - Переверзєва, О.В. (SWorldJournal, 2022)
The abstracts provide suggestions for the work of the accompanist in terms of distance education: the use of a digital library of choral works; making audio files using an audio editor; performing work on adapting the score of a musical work to work with